Comparison of the sealing ability of biodentine, iroot bp plus and mineral trioxide aggregate - KARTAL, NEVİN; CİMİLLİ, ZÜHRE HALE (Cumhuriyet University Faculty of Dentistry, 2016)
Objective: The aim of this study was to compare the sealing ability of two new root repair materials, Biodentine and iRoot BP Plus against ProRoot MTA when used as root-end fillings. Methods: The root canals of 45 extracted maxillary anterior teeth were prepared with Pro Taper instruments. After apical resection and ultrasonic root-end cavity preparation, the teeth were divided into three groups. The cavities in the first group of 15 were filled with Biodentine, the second with iRoot BP Plus and the third with ProRoot MTA. A computerized fluid filtration method assessed the seal at 2, 10 and 28 days. Results: Significant differences were found between Groups 1-2, Groups 1-3 and between Groups 2-3 at all-time intervals (P < 0.05). Leakage was not significantly different at 10 and 28 days for Biodentine and iRoot BP Plus (P > 0.05). Conclusion: The two new root repair materials showed good performance and both offered improved handling properties compared to MTA. © 2016, Cumhuriyet Dent J. All rights reserved.
Keywords: Bioceramic root repair material; Calcium silicate-based cement; Endodontics; MTA; Root-end filling